Prevalence and distribution of human papillomavirus genotypes in Chinese women between 1991 and 2016: A systematic review. Issue 6 (June 2018) - Zhou, Hong-Lu; Zhang, Wei; Zhang, Can-Jing; Wang, Song-Mei; Duan, Ya-Chen; Wang, Jin-Xia; Yang, Huan; Wang, Xuan-Yi
Highlights: This is the latest analysis on China-specific distribution of carcinogenic HPV types. A dozen of HPV vaccines utilized uneven types are being developed in China. The top 10 types in Chinese ICC patients were HPV 16, 18, 58, 52, 33, 31, 55, 68, 53 and 45. The prevalence of HPV infection peaked between 20 and 24 years with a rate of 24.3%. The second peak of prevalence was observed among women aged 45–55 years in less developed regions. Abstract: Background: Human papillomavirus (HPV) associated cervical cancer is one of the most common cancers and ranked as the eighth most common killer for Chinese women. A dozen of HPV vaccines are being developed in China without a solid China-specific distribution of carcinogenic HPV types, thus, we performed this systematic review to explore the China-specific spectrum of high-risk types causing cancer. Methods: Studies on HPV infection among Chinese women were searched. All retrieved articles were screened and reviewed by a standardized algorithm. Distribution of carcinogenic HPV types and age-specific prevalence were analyzed using random-effects model. Results: A total of 303 articles were included in the final analysis. The top 10 common HPV types detected in ICC patients, in descending order of frequency, were HPV 16 (62.5%), 18 (12.4%), 58 (8.6%), 52 (5.7%), 33 (4.6%), 31 (3.5%), 55 (2.4%), 68 (2.4%), 53 (2.2%) and 45 (2.0%) respectively. Similar spectrum was found in women with precancer. The prevalence of HPV infection peaked between 20 and 24 years with a rate of 24.3%, thereafter declined substantially and stabilized at middle-ages. Compared to women living in the developed provinces, the second peak was observed among women aged 45–55 years in less developed regions. Conclusion: In general, the spectrum of HPV types in women with precancer/cancer and the pattern of age-specific prevalence were consistent with that of elsewhere worldwide. However, some distinguished characteristics could also be concluded, and these imprinting should be considered and integrated when developing vaccines and strategy for disease control in China.